The Influence of environmental mindsets and cultural values on sustainable behavior intentions - Anggraeni, Ary Yunita; Bakhtiar, Yohan; Jyuhn Wang, Hurng; Tse Hou, Tony Chieh (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2024)
This study explores the interplay between long-term orientation traditions, strategic planning, and their influence on Generation Z mindset and environmental sustainability concerns in Indonesia. This study investigates how cultural values and future-focused behaviors shape attitudes toward ecological responsibility. Data collection was conducted through an online questionnaire targeting students from private universities across various Indonesian regions, providing a diverse perspective. Using advanced analytical methods with SmartPLS, the study reveals that Generation Z in Indonesia exhibits a significant awareness of and engagement with environmentally themed initiatives. These findings highlight the generational shift toward prioritizing sustainability within societal and cultural contexts. The research contributes theoretically and practically by enhancing the understanding of generational dynamics in sustainability efforts and offering actionable insights for policymakers, educators, and environmental organizations. Ultimately, it underscores Generation Z's potential as a key driver of sustainable development, aligning with Indonesia’s long-term environmental goals.